1997
DOI: 10.1111/j.1365-2389.1997.tb00570.x
|View full text |Cite
|
Sign up to set email alerts
|

The phosphorus composition of soil solutions and soil leachates: Influence of soil:solution ratio

Abstract: Compositional differences between soil solutions obtained by different methods have frequently been reported; variations in the soi1:solution ratio may explain these results. In this study we compared the amount and composition of phosphorus (P) in soil leachates and soil solutions from a temperate grassland soil in northeast Scotland and determined the influence of soi1:solution ratio on P fractions in soil water extracts. Leachates were collected from intact soil cores over 6 months, the cores were then dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 27 publications
1
20
0
2
Order By: Relevance
“…However, expressed on a soil-weight basis, mineral-soil P w MUP increases noted here (averaging 10.13mg P kg − 1 ) were considerably greater than increases reported for UK lowland pasture soils by Turner and Haygarth (2001) (< 1 to 5.5mg P kg − 1 ) and for 2 Australian pasture soils as reported by (1.17 and 0.62mg P kg − 1 ). Chapman et al (1997a) found that the soil/water ratio used in P w analyses had little effect on the quantity of P w MUP extracted. Comparatively high P w MUP increases in this study therefore indicate that Irish grassland soils contain particularly large quantities of organic and fine colloidal P susceptible to dryinginduced solubilisation.…”
Section: Organic and Colloidal P Releasementioning
confidence: 93%
“…However, expressed on a soil-weight basis, mineral-soil P w MUP increases noted here (averaging 10.13mg P kg − 1 ) were considerably greater than increases reported for UK lowland pasture soils by Turner and Haygarth (2001) (< 1 to 5.5mg P kg − 1 ) and for 2 Australian pasture soils as reported by (1.17 and 0.62mg P kg − 1 ). Chapman et al (1997a) found that the soil/water ratio used in P w analyses had little effect on the quantity of P w MUP extracted. Comparatively high P w MUP increases in this study therefore indicate that Irish grassland soils contain particularly large quantities of organic and fine colloidal P susceptible to dryinginduced solubilisation.…”
Section: Organic and Colloidal P Releasementioning
confidence: 93%
“…Menzies and Bell, 1988;Zabowski and Ugolini, 1990;Sheppard et al, 1992;Dahlgren, 1993;Lorenz et al, 1994;Giesler et al, 1996;Chapman et al, 1997). Most studies are fairly consistent in their illustration of the differences among methods in terms of element concentrations in pore water, partly due to different fractions of pore waters considered.…”
Section: Uses and Limitations For Soil Pore Water Extractionsmentioning
confidence: 91%
“…Extraction procedures have also been developed for the determination of the anionic species in soils of elements such as sulfur which are important as binding sites for metals as well as for its own mobility and availability (Cordos et al, 1995). The important biosignificant element selenium has similarly received attention (Blaylock and James 1993;Seby et al, 1997) and procedures for the speciation of phosphorus have been developed (Vaz et al, 1992;Chapman et al, 1997).…”
Section: Other Selective Extraction Methodsmentioning
confidence: 99%